The impact of a political shock on foreign exchange markets in a small and open economy: A dynamic modelling approach - Ibrahim A. Onour; Bruno S. Sergi (Journal of Central Banking Theory and Practice, 2021)
This paper aims to analyse the dynamics of foreign exchange markets in a country facing political uncertainty that prompt capital outflow from the country. The economic environment under investigation is characterized by dual foreign exchange markets: a formal or official market for foreign exchange with insufficient and volatile foreign exchange flows, and a strong and thriving informal market, with a higher exchange rate2. The findings in the paper indicate a necessary condition for stabilization of the exchange rate system and that is that the return on investment should exceed the depreciation rate of domestic currency in the formal foreign exchange market. This condition implies that the return on investment should at least compensate investors for the opportunity cost of holding domestic money in their private portfolio wealth. Our findings also indicate that stability of the foreign exchange rates is more difficult to achieve under insufficient official reserves as the recovery process from a shock becomes more costly in terms of time period needed for the adjustment process to complete. The dynamic path of the foreign exchange premium shows that under massive capital outflow caused by economic sanctions, the informal market exchange rate overshoots the equilibrium stationary exchange rate, and the size of such overshooting depends on the size of available foreign exchange reserves held by the central bank.
Keywords: F31; E52; E58; C32; 330; dynamic model; foreign exchange markets; political uncertainty; stability analysis; economic sanctions